Implementation Of Human Resource Management in Supporting the Development of Artists’ Creativity - Abduh, Muhammad; Rusydi, Muhammad; AC, Ahmad (Borong Newinera Publisher, 2026)
This paper seeks to examine how human resource management can be implemented to facilitate the process of nurturing the creativity of artists in the context of Al Hasyimi Calligraphy Art Studio in Palu City, Central Sulawesi. A qualitative descriptive method was used in the study to get to know the managerial practices and creative development in the natural environment of the studio. Participant observation, in depth interviews, and documentation were used to collect data that included the studio leader, trainers and active members. The interactive model of data reduction, data display, and conclusion drawing was used to analyze the data. The results reveal that the practices of human resource management applied in Al Hasyimi Calligraphy Art Studio are characterized by adaptive planning, open-based recruitment that is based on interest and commitment, life-long training and mentoring, and moral and religious-based supervision. They are not structured in a very formal system but they are effective in providing an environment that is conducive to artistic learning and development of creativity. The research also established that commitment to leadership, an enabling organizational environment and the intrinsic motivation of the members are critical aspects that reinforce creativity. Simultaneously, the lack of financial resources, poorly equipped facilities, and a lack of a well-established career development system are serious problems. The research concludes that creativity can be supported effectively through human resource management in a community based artistic institution provided that it is based on commitment, mentorship and shared values.